Development, validation and application of a Brazilian knowledge scale about sports doping in dentistry - Lucas Alves JURAL; Thais Rodrigues Campos SOARES; Raildo da Silva COQUEIRO; Tiago Braga RABELLO; Matheus Melo PITHON; Lucianne Cople MAIA (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract To evaluate the knowledge of Brazilian dentists of sports doping through the development, validation and application of the Brazilian Knowledge Scale about Sports Doping in Dentistry (B-KSSDD). A scale with 12 items was developed to assess a dentist's ability to determine whether the use of a medication characterised sports doping according to the World Anti-Doping Agency. A preliminary study to validate the B-KSSDD was carried out with 135 dentists, allowing the evaluation of ceiling and floor effects, convergent and discriminant validity, test-retest reliability and internal consistency of the instrument. A sample size calculation using the results of the preliminary study and the B-KSSDD was completed online using SurveyMonkey® by 270 participants from all regions of the country. The B-KSSDD showed evidence of convergent and discriminant validity, good temporal stability (ICC = 0.75) and internal consistency (alpha = 0.89). In the main study, the participants obtained an average score of 4.19/12 points on the B-KSSDD, suggesting that these professionals have insufficient knowledge about sports doping. The age of participants showed a negative association with knowledge about doping, while frequency of treating athletes and frequency of performing surgeries showed positive associations with knowledge about doping. The dentists had insufficient knowledge of the subject. Age of participants and frequency with which they attend to athletes are associated with knowledge about sports doping. Professional updating and education policies on doping are necessary for dentists, as athlete patients are at risk for severe sporting and financial penalties.